2020
DOI: 10.1128/msystems.00827-19
|View full text |Cite
|
Sign up to set email alerts
|

Galacto-Oligosaccharides Modulate the Juvenile Gut Microbiome and Innate Immunity To Improve Broiler Chicken Performance

Abstract: Improvements in growth performance and health are key goals in broiler chicken production. Inclusion of prebiotic galacto-oligosaccharides (GOS) in broiler feed enhanced the growth rate and feed conversion of chickens relative to those obtained with a calorie-matched control diet. Comparison of the cecal microbiota identified key differences in abundances of Lactobacillus spp. Increased levels of Lactobacillus johnsonii in GOS-fed juvenile birds at the expense of Lactobacillus crispatus were linked to improved… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 93 publications
4
25
1
1
Order By: Relevance
“…The authors speculated that this could have been due to an increase in passage through the gastrointestinal tract, which might contribute to lower nutrient utilization. Our findings are in accordance with those presented by Midilli et al [18], who reported that prebiotic supplementation did not significantly affect chicken BW, whereas other reports have demonstrated that different prebiotics may improve growth performance [19,20]. The possible disparities among the reports of bird responses could be due to differences in the bird strain, age, or sex, the nutrient composition of the diet, the gut microbiome activity response, the level of additive inclusion, the duration of supplementation and/or other environmental and management conditions between the studies.…”
Section: Bird Performancesupporting
confidence: 93%
“…The authors speculated that this could have been due to an increase in passage through the gastrointestinal tract, which might contribute to lower nutrient utilization. Our findings are in accordance with those presented by Midilli et al [18], who reported that prebiotic supplementation did not significantly affect chicken BW, whereas other reports have demonstrated that different prebiotics may improve growth performance [19,20]. The possible disparities among the reports of bird responses could be due to differences in the bird strain, age, or sex, the nutrient composition of the diet, the gut microbiome activity response, the level of additive inclusion, the duration of supplementation and/or other environmental and management conditions between the studies.…”
Section: Bird Performancesupporting
confidence: 93%
“…Synbiotics may be more efficient than prebiotics and probiotics, as synbiotics are a synergistic mixture of probiotics and prebiotics. Probiotics are live microorganisms that improve the survival and implantation of live beneficial microbes in the gut, either by metabolically activating or by the stimulation of beneficial bacteria [30], and prebiotics are nondigestible fiber compounds that have a useful influence on the host by selectively enhancing the survival and growth of healthy microbial species in the gut [31,32]. Several synbiotics [33][34][35] have been used as growth promoters and immune enhancers to increase production and health in broilers under both thermoneutral and hot ambient temperatures [36], while other synbiotics [37,38] had no effect on stress reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include use of natural plant-derived products such as carvacrol [38], addition of dietary prebiotics [39] and administration of live probiotic bacteria [40]. More recently, prebiotic galacto-oligosaccharides (GOS) have been added to broiler feed and enhanced the growth rate and feed conversion of chickens relative to those obtained with a calorie-matched control diet [41]. Recent developments have observed chicken diets enriched with Omega-3 PUFA's for benefits to human health [5].…”
Section: Discussionmentioning
confidence: 99%